(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
The advent of modern technologies and the Internet has accelerated the exchange of information between people. The uniform distribution of information, news and scientific research results has a positive effect on the progress of humanity. With the growing use of Modern innovative technologies in public life, the concept of "information society" has emerged.